Akselerasi UMKM Madu Melalui Strategi Kurasi dan Inkubasi Berkualitas dalam Mendukung Pembangunan Daerah Kabupaten Gorontalo - Muhammad Fuad Alamsyah; Zulkarnain Ilyas Idris; Andi Subhan (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2026)
This study aims to analyze the implementation of product curation and business incubation strategies in accelerating the development of Madu Azwa Suwawa MSMEs in Gorontalo Regency. The study employed a qualitative approach with a case study design through interviews, observations, documentation, and Focus Group Discussions (FGD). The results showed that product curation was able to improve product quality, packaging, branding, and consumer trust in local honey products. Meanwhile, business incubation contributed to strengthening business management, financial recording, digital marketing, and the expansion of business networks. The implementation of these two strategies had an impact on increasing the number of customers, expanding market access, and increasing business turnover. The findings indicate that the integration of curation and incubation is an effective MSME acceleration model in enhancing competitiveness and supporting sustainable local economic development based on regional potential.